Model Sensitive in Numerical of the Formation of Typhoon Robyn (1993) - Kevin K. W. Cheung Russell L. Elsberry (Terrestrial, Atmospheric and Oceanic Sciences, 2006)

(untitled)
The PSU-NCAR mesoscale model MM5 with an 81-km (27-km) resolution coarse (fine) grid is used to simulate the formation of Typhoon Robyn (1993) in the western North Pacific. This study examines the roles of mesoscale convective system (MCS) during Robyn’s formation, and also focuses on the sensitivity of the simulations of Robyn’s intensification to the choice of cumulus parameterization, planetary boundary layer (PBL) parameterization, and the explicit moisture scheme in the model.